Recent advances regarding changes in quality and fine structure of starch during rice aging - GU Yue; LI Xinyu; BAO Jinsong (浙江大学学报. 农业与生命科学版, 2024)
Rice (Oryza sativa L.) is one of the most widely cultivated cereal crops in the world and plays a vital role in global food security. Aging is a natural phenomenon that occurs during the storage of rice grains and the mechanisms are still not completely understood. During the storage of rice, the physicochemical properties of sensory, cooking and gelatinization, and starch structure and function change to different degrees. These changes are closely related to storage time and temperature and have irreversible impacts on rice quality. While the changes in physicochemical properties caused by rice aging have been intensively investigated, few studies have focused on changes in starch fine structure following storage. This review examined the types and methods of artificial aging as well as their extensive effects on physicochemical properties and changes in starch fine structure, which provides a theoretical basis for further elucidation of rice aging mechanisms.